The rebirth of urban public space? - García Doménech, Sergio; Martí-Ciriquián, Pablo (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2013)
The current global economic crisis seems to have returned to the role of public space in the cities. First, the claimed role of public space is reborn. In addition, civic use of public space has been boosted in opposite to skewed perception of private collective spaces, prevalent in recent years. Using three recent episodes of the evolution of public space in Spanish society, this article presents three approaches about public space: political control, social claim and civic use. After a period of decline and subsequent dominance of the private in the city, the citizenship status has boosted again the public space as social space par excellence. It concludes by highlighting the opportunity to recover the urban place and the need to enhance the role that public space must continue to play in the complexity of the city.
Keywords: public space; citizenship; political control; urban claims; public spirit